The current situation of health equity in underserved areas of Afghanistan - Salem, Marwa Rashad; Hegazy, Nelly; Eldeeb, Sherif; Shaguy, Jerome A.; Nassery, Ramesh Mohammad; Khawari, Abdullah; Tanoli, Jamshed; Abouzeid, Alaa (Frontiers in Public Health, 2024)
Background In Afghanistan, providing universal health coverage (UHC) in accordance with the principles of the UHC declaration is challenging on two fronts: the geographic topography of the country and the prevailing gender dynamics within the local culture. Methods We conducted a desk review of underserved areas in the context of health services by gathering and analyzing existing literature, reports, and data using a combination of keywords and phrases such as: “underserved areas,” “healthcare disparities,” “access to healthcare,” and “health services.” The primary data were derived from an analysis of underserved populations conducted by the World Health Organization (WHO) Afghanistan's Emergency Program, supplemented by information from in-country partners. In addition to other reports, this review focused on analyzing the geographical availability of primary healthcare (PHC) services by employing the guidelines set forth in the SPHERE framework. It also took into account the social dynamics within the Afghan population that may create barriers to equity in terms of demand and access to PHC services. Results Although there are a significant number of primary healthcare facilities in operation (4,242), they are unevenly distributed across different regions of Afghanistan, resulting in almost 25% of the population being underserved. The underserved population is nearly equally distributed between genders, with the majority residing in rural communities. Women of childbearing age represent 28% of the underserved population. Children under the age of five represent 16–18% of the underserved population in all regions, except in the western region, where they represent between 12 and 13%. Individuals over 60 years of age represent 1–3% of the underserved population across all regions. More than 50% of the population in the Central Highlands of Afghanistan is underserved, followed by the western and southern regions. Ghor province in the western region has the highest proportion of underserved populations, followed by Zabul province in the southern region. Conclusion Afghanistan is currently experiencing a protracted humanitarian crisis, with millions of people living in poverty and lacking access to healthcare. This situation exposes them to serious risks such as disease epidemics, starvation, and maternal and child mortality. It is crucial to implement alternative strategies to reach the most affected populations and to increase funding for the delivery of healthcare services in Afghanistan.